0331 Intersectional discrimination and sleep health among women veterans: a pilot study. (25th May 2022) - Agrawal, Alpna; Moghtaderi, Isabel; Kelly, Monica; Carlson, Gwendolyn; Lee, Diane; Mitchell, Michael; Zeidler, Michelle; Alessi, Cathy; Sung, Yeonsu; Hamilton, Alison; Bean-Mayberry, Bevanne; Yano, Elizabeth; et al.
Abstract: Introduction: Structural inequalities perpetuate poor health outcomes. Sleep inequality, which is the disproportionate burden of sleep problems among marginalized groups compared to historically advantaged groups, is poorly understood. While racial discrimination is associated with chronic health outcomes, few studies have examined the health impact of discrimination stemming from multiple social vulnerabilities. The current study assessed women veterans' experiences of intersectional discrimination, specifically the combined impact of gender and racial/ethnic discrimination on sleep health. Methods: Data were from the WISE (Women Improving Sleep through Education) study. Participants were women veterans with a previous diagnosis of sleep apnea or 1 or more risk factors for sleep disordered breathing (n=39). Data collection was from 3/2021–11/2021. The 9-item Major Discrimination Scale (MDS) and 10-item Everyday Discrimination Scale (EDS) were employed. The MDS included items such as "have you ever been unfairly stopped, searched, questioned, physically threatened or abused by police?" and the EDS, "how often on a day-to-day basis are you treated with less courtesy than other people?". Items were adapted to assess discrimination related to respondents' gender and race/ethnicity separately. Major intersectional discrimination (MDS-gender + MDS-race/ethnicity) and everyday intersectional discrimination (EDS-gender + EDS-race/ethnicity) were computed. Sleep health was assessed by the Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI). Descriptive statistics and correlational analyses were performed. Results: Racial/ethnic minority women veterans comprised 54% of the study sample. Prevalence of major intersectional discrimination was 67% and everyday intersectional discrimination, 92%. Compared to other racial/ethnic groups, the proportion of Black women veterans reporting major intersectional discrimination was highest (78%). Major intersectional discrimination was positively correlated with ISI (p=0.04) and PSQI (p=0.01). Everyday intersectional discrimination was not correlated with sleep health (p>0.05). Conclusion: Pilot study findings highlight the potential role of discrimination on sleep health, particularly multiple forms of discrimination. High prevelence of intersectional discrimination related to women veterans' gender and racial/ethnic identities was observed. Major intersectional discrimination, not everyday intersectional discrimination, was associated with higher insomnia severity and poorer sleep quality. Support (If Any): LIP VA HSRD IIR16-244, RCSA20-191, LIP65-177, NIH/NHLBI K24HL143055, VAGLAHS GRECC, VAGLAHS CSHIIP, RCS 21-135, CIN 13-417, RCS 05-195